Multiple Ecological Niche Modeling Reveals Niche Conservatism and Divergence in East Asian Yew (Taxus) - Chuncheng Wang; Minqiu Wang; Shanshan Zhu; Xingtong Wu; Shaolong Yang; Yadan Yan; Yafeng Wen (Plants)
Understanding ecological niche evolution patterns is crucial for elucidating biogeographic history and guiding biodiversity conservation. Taxus is a Tertiary relict gymnosperm with 11 lineages mainly distributed across East Asia, spanning from tropical to subarctic regions. However, the spatiotemporal dynamics of its ecological niche evolution and the roles of ecological and geographical factors in lineage diversification, remain unclear. Using occurrence records, environmental data, and reconstructed phylogenies, we employed ensemble ecological niche models (eENMs), environmental principle components analysis (PCA-env), and phyloclimatic modeling to analyze niche similarity and evolution among 11 Taxus lineages. Based on reconstructed Bayesian trees and geographical distribution characteristics, we classified the eleven lineages into four clades: Northern (T. cuspidata), Central (T. chinensis, T. qinlingensis, and the Emei type), Western (T. wallichiana, T. florinii, and T. contorta), and Southern (T. calcicola, T. phytonii, T. mairei, and the Huangshan type). Orogenic activities and climate changes in the Tibetan Plateau since the Late Miocene likely facilitated the local adaptation of ancestral populations in Central China, the Hengduan Mountains, and the Yunnan–Guizhou Plateau, driving their expansion and diversification towards the west and south. Key environmental variables, including extreme temperature, temperature and precipitation variability, light, and altitude, were identified as major drivers of current niche divergence. Both niche conservatism and divergence were observed, with early conservatism followed by recent divergence. The Southern clade exhibits high heat and moisture tolerance, suggesting an adaptive shift, while the Central and Western clades retain ancestral drought and cold tolerance, displaying significant phylogenetic niche conservatism (PNC). We recommend prioritizing the conservation of T. qinlingensis, which exhibits the highest PNC level, particularly in the Qinling, Daba, and Taihang Mountains, which are highly degraded and vulnerable to future climate fluctuations.